Dietary factors as the major determinants of overweight and obesity among Iranian adolescents. A cross-sectional study - Hatami, Monireh; Mohd Taib, Mohd Nasir; Jamaluddin, Rosita; Abu Saad, Hazizi; Djazayery, Abolghasem; Chamari, Maryam; Nazari, Mojgan (Elsevier, 2014)
This study investigated the determinants of overweight/obesity in adolescents. A cross-sectional survey was carried out on 1157 adolescents. Weight and height were measured. Information on socio-economic status (SES), dietary intakes, physical activity, and sedentary behaviours were collected by a self-administered questionnaire. Binary and multivariate binary logistic regressions were used to obtain the relationships and odds-ratios, respectively. The prevalence of overweight and obesity was higher among adolescents in low- or high-income families, adolescents whose mothers worked out of home, adolescents whose parents were both overweight, adolescents who watched a lot of TV or had excessive energy intake, adolescents with lower physical activity or lower intake of dietary fibre, those who skipped breakfast ≥4 times per week, and those with low and high fat intake. However, multiple logistic regression analysis showed that only energy intake was associated with increased odds and vegetables and fibre intake were associated with a reduction in the odds of being overweight (all p < 0.05). Adolescents from middle SES showed a lower risk of overweight/obesity than low and high SES due to better dietary intakes and less sedentary behaviours. Therefore, in overweight/obesity prevention programs, adolescents with determined risk factors from families with low and high SES should receive attention.